Republic of Tajikistan : Poverty Reduction Strategy Paper Second Progress Report. (IMF Staff Country Reports; Country Report, 2006)
This Second Progress Report on Tajikistan's Poverty Reduction Strategy Paper (PRSP) discusses key developments in the status and dynamics of poverty-related indicators in the country during 2004. Although economic growth has generated significant reductions in poverty rates in the past years, the report concludes that people's livelihoods have not changed drastically. Income poverty remains high. People's access to energy, water, communications, education, and health services remains highly problematic. This report also reviews the government's macroeconomic management performance and discusses institutional shortfalls affecting the poverty reduction effort.